Qualities of transformative leaders in WASH: A study of gender-transformative leadership during the COVID-19 pandemic - Gonzalez, Diana; Carrard, Naomi; Chhetri, Aastha; Somphongbouthakanh, Phetsakhone; Choden, Tshering; Halcrow, Gabrielle; Budhathoki, Ratan; Wangchuk, Ugyen; Willetts, Juliet (Frontiers in Water, 2022)
Equal access to water, sanitation and hygiene (WASH) for all requires leadership that prioritises and drives inclusion. Inclusive WASH also presents opportunities to advance equality more widely, with WASH a pathway to meaningful participation and empowerment for diverse groups. The concept of gender-transformative leadership – which connects ideas of leadership to transformative models of gender equality in development theory that challenge prevailing power structures – is a relevant lens for exploring inclusive WASH. This article shares findings and reflections from a positive deviance study that aimed to investigate gender-transformative leadership in the WASH sector to explore (i) the factors shaping gender-transformative leadership and the characteristics of gender-transformative leaders; (ii) actions taken by gender-transformative leaders; (iii) the types of outcomes achieved; and (iv) ways to strengthen gender-transformative leadership. The study was undertaken during the COVID-19 pandemic in Bhutan, Lao People’s Democratic Republic, and Nepal. We developed a conceptual framework which considers leaders' (i) personal values and traits; (ii) leadership styles; (iii) actions; and (iv) outcomes, influenced by a range of (v) enabling factors and barriers. Interviews with 19 leaders highlighted their strong learning orientation, social justice values, humility, courage, and altruism. Leadership styles were primarily empathetic, with leaders guided by a mission to lead by example and pursue equality in their professional and personal lives. Exploration of actions and outcomes revealed a range of inclusion-oriented WASH activities responding to pandemic-related challenges, with associated potential outcomes in shifting norms. However, validation of outcomes was not possible due to the study timeframe and complexity of tracing complex social change in a positive deviance study reliant on self-reporting. Analysis of enablers and barriers to gender-transformative leadership respectively emphasised the importance of educational opportunities and the persistence of traditional gender norms. Findings contribute to the body of knowledge on gender-transformative leadership, being the first study to connect this concept to WASH. Future research could build further evidence by applying the conceptual framework to analyse additional contexts or sectors, and by more fully articulating and validating outcomes in terms of their potential for gender-transformative leadership to drive equality both in and beyond WASH.